Fuzzy-reliability engineering: - Verma, A. K. (Narosa Publishing House, 2007)
Fuzzy-reliability is a novel concept in systems engineering as fuzzy sets can capture subjective, uncertain and ambiguous information. This text focuses on fuzzy set based concepts and its applications. Various concepts such as probist, profust, fuzzy event based method, fuzzy fault tree analysis, transformations and hybrid approaches have been described. Applications in systems reliability, availability and maintainability, software reliability and power system reliability have been discussed in depth. Maintenance issues described in this text relate to fuzzy availability modeling for Markov and semi-Markov models, fuzzy dynamic reliability evaluation under imperfect repair and maintenance strategy selection using fuzzy linguistics. Software reliability using fuzzification of cost model parameters like penalty, warranty and risks are applied to the existing growth models. Composite power system reliability modeling using fuzzy sets and fuzzy confidence intervals with fuzzy linear programming for minimization of load curtailment has demonstrated the flexibility and capability of using fuzzy sets in reliability engineering. This book is one of the few on the subject of fuzzy-reliability engineering